THE PREVALENCE OF THE FEMALE ATHLETE TRIAD COMPONENTS AND RISK FACTORS IN ATHLETES AND DANCERS - Arroyo, Julia Pearl M. (Stadium - Hungarian Journal of Sport Sciences, 2024)
Purpose: The female athlete triad is a condition of low energy availability, menstrual dysfunction, and low bone mineral density common to dancers and weight-class sports athletes. This study aimed to investigate the prevalence of the female athlete triad components and risk factors. The components and risk factors were discussed in light of the sources of nutritional information and factors that affected the daily dietary intake of female athletes and dancers. Materials and Methods: Fifty-four (54) female athletes and dancers (18.96 ± 3.49 years old) answered a survey questionnaire about years of formal dance or sports training, sources of nutritional information, factors that affected their daily food choices; menstrual history, and injury history. Energy availability was estimated using the Low Energy Availability in Females Questionnaire (LEAF-Q; MELIN, et. al., 2014). Results and Conclusion: Twenty-one participants (38.90 %) had a risk of low energy availability, while 28 participants (51.90 %) had menstrual dysfunction. Twenty participants (37%) had a history of musculoskeletal injuries. The mean body mass index was 20.46 ± 4.08 and the mean percent body fat was 18.19 ± 5.73%. The primary sources of nutritional information were coaches, peers, and magazines. Personal preference, convenience, and parents were the main factors that affected daily food choices. The prevalence of the Female Athlete Triad components and risk factors was relatively high. The presence of the components and risk - factors should alarm coaches, trainers, and parents for further tests and proper intervention measures.